A Comparison between Intravenous and Intraumbilical Vein of Oxytocin in Management of Third Stage of Labor - يوسف أحمد; ديوب ميسون; عبدالله ربا (Latakia University Journal -Medical Sciences Series, 2020)
Background and objective: Reducing the time of delivery of placenta through active management of third stage can prevent uterine atony and postpartum hemorrhage. A comparison between intravenous and intraumbilical vein of oxytocin in management of third stage of labor to determine the best way to inject oxytocin during the third stage of labor. Patients and methods: This case series study was conducted on 200 women divided in two group each had 100 parturient. All the patients having uncomplicated labor reaching 3rd stage of labor. Group 1 received 20 units of oxytocin mixed with 20 ml of normal saline through intraumbilical vein. Group 2 received oxytocin intravenous infusion (20 units oxytocin mixed with 500 ml normal saline). In both groups the duration of 3rd stage in minutes, amount of blood loss in milliliters and complications were documented. Results: Most of the patients were with age group of 19-34 years. Blood loss was markedly decreased in group 1 230± 89.9 ml in contrast to group 2 309.2± 124.6 ml. Third stage of labor markedly decreased in group 1 2.67± 1.3 minutes as compared to group 2 4.38 ± 2.9 minutes. Conclusion: Intraumbilical vein injection of oxytocin in the management of third stage of labor is safe and effective.